Developing Web-Based Archiving System with XP: Study Case on UPT Kearsipan Universitas Sam Ratulangi - Egidius C. Runtu; Eric Alfonsius; Benny Pinontoan (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
UPT Kearsipan Universitas Sam Ratulangi, a technical implementation unit responsible for archive management, faces challenges with traditional manual correspondence processes, leading to potential data loss, recording errors, and slow information distribution. This research aimed to develop a web-based Archiving Correspondence Information System (ARCIS) to address these issues. The system was developed using the Extreme Programming (XP) method, emphasizing frequent iterations, active user involvement, and continuous testing. Built with PHP and MySQL technologies, ARCIS includes features such as incoming and outgoing letter management, disposition tracking, classification, institution and user data management, and notification alerts. The XP method, with its rapid adaptation to changing user needs, was chosen to create a responsive and high-quality solution. Black box testing confirmed that all system functionalities perform effectively and meet user needs, achieving a 100% success rate in Iteration 1 and 83.33% in Iteration 2. This system provides a more effective, efficient, and organized solution for managing letters and archives.